(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To quantitatively assess the changes in dental arch dimensions in orthodontic patients who underwent extraction of premolar teeth, using analysis software on digital dental models generated by an intraoral 3D scanner system. Methods: A retrospective study was conducted on 27 patients who completed orthodontic treatment at Nhu Ngoc Dental Clinic. The 3D scan data of both upper and lower arches (.STL files) before treatment (T0) and after treatment (T1) were measured using digital software to compare the following dimensions: canine interproximal width, molar interproximal width, arch length, and arch perimeter. Results: The study observed a significant reduction in arch length and perimeter after orthodontic treatment (p < 0.05). However, the inter-canine width tended to remain stable, indicating that the dental arch was not narrowed in the anterior region. In contrast, the inter-molar width significantly decreased due to the loss of physiological anchorage. Conclusion: Premolar extraction in orthodontic treatment primarily affects the anterior-posterior arch dimensions and the posterior region’s width. However, the canine interproximal width is preserved, contributing to maintaining the aesthetic of the smile.